Effect of Social Capital on Rural Household Welfare in Southwestern Nigeria (2013)
Rural household welfare remains low in Nigeria, as the traditional capital (physical, natural, human and financial) has not fully led to its improvement. There is increasing shift of attention to social capital as an element that explains household welfare. The nexus between social capital and rural household welfare in southwestern Nigeria has not been fully examined. The effect of social capital on rural household welfare in southwestern Nigeria was therefore investigated. Multistage sampling technique was used. Oyo and Ekiti states were selected from the six states in southwestern Nigeria based on their poverty profile (the least poor and the poorest). Six rural Local Government Areas and thirty-two communities were selected from the two states based on probability proportionate to size and sample size of 298 was used for the analysis. Data were collected on household demographic characteristics such as age, education and household size, expenditure profile and social capital dimensions: Membership Density (MD), Decision Making (DM), Meeting Attendance (MA), heterogeneity, Cash Contribution (CC) and Labour Contribution (LC). Data were analysed using descriptive statistics, ordered probit, ordinary least square, two-stage least square and control function regression models at p=0.05. Ninety three percent of the households were headed by male. Mean age, years of formal education and household size were 48.3 ± 11.7 years, 8.4 ± 6.3 years and 6.1 ± 2.6 respectively. Average MD and DM in association were 4.5 ± 2.1 and 24.7 ± 13.2. Households attended four out of every five meetings scheduled. Diversification of membership measured by heterogeneity index was 21.7 ± 16.4 while annual CC and LC to association were N7,412.95 ± N9,757.73 and 54.6 ± 18.4 mandays respectively. Membership in religious group accounted for the highest proportion (77.3 percent) while recreational club accounted for the lowest (4.67 percent). The highest Welfare Tercile (WT) had monthly mean per capita expenditure of N9,135.98  N4,014.35 which was four times the value for the lowest WT (N2,239.82  N958.33). The maximum CC to associations was recorded by the highest WT (N9,756.90 ± N12,358.25) while the lowest WT had the maximum LC of 24.7 ± 20.2 mandays. Majority of the households (78.0 percent) benefited from access to information on market outlets and share of risk/shocks while 55.5 percent had access to land. Low educational level reduced benefit derived from social group by 0.027, while being a farmer (0.404), LC (0.016) and DM increased benefit received from social group. Household welfare reduced with increase in age (-2.965), being married (-2.965), household size (-0.398), being a farmer (-1.676) and LC (-7.5x10-4). Conversely, age squared, education and DM index increased household welfare by 0.2 percent, 10.8 percent and 2.8 percent respectively. Aggregate social capital index increased household welfare by 9.5 percent, while controlling for non-linear interaction of social capital with unobservable variables further increased the effect of social capital by 13.1 percent. Decision making and aggregate social capital improved household welfare while labour contribution reduced it. A bi-causality relationship existed between social capital and household welfare.